Socialization of the Use of Google Gemini to Improve the Quality of Financial Management and Marketing of MSMEs in Indonesia: Penelitian - Nadjah Thalib; Dewi Mariam Widiniarsih; M.Pahlan; Dinesh Basti Farani; Vidya Ramadhan Putra Pratama (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity aims to improve the quality of Financial Management and Digital Marketing of Micro, Small, and Medium Enterprises (MSMEs) through socialization and intensive training on the use of Google Gemini (Generative AI Model). MSMEs in the focus areas (Merauke, South Sumatra, Central Java, Makassar, and Palangkaraya) often face bottleneck challenges in accurate financial recording and creating effective marketing content strategies, which limits their growth and competitiveness. The PkM program was implemented for ten days in the month of [Mention Month/Year of PkM] with a blended training method (virtual and limited face-to-face) and specific case mentoring .The PkM participants consisted of 150 MSMEs (30 participants per location) operating in the service, trade, and processing sectors. The training materials covered (a) the use of Gemini to create daily cash report templates and calculate the cost of goods sold (COGS); and (b) the use of Gemini to formulate marketing content and copywriting strategies tailored to the local target market. Evaluation was conducted through measuring the increase in AI-Financial and AI-Marketing literacy (pre-test and post-test) as well as output prototypes (simple financial reports and marketing campaigns ) produced by participants. The PKM results showed a significant increase in participants' understanding of the Gemini application for both functions (the average post-test score increased≈ 38%compared to the pre-test). Participants successfully created a more structured daily cash report prototype and a more creative marketing campaign . This activity concluded that Google Gemini functions as a user-friendly and effective management tool , capable of quickly overcoming administrative and creative challenges for MSMEs, ultimately supporting increased operational efficiency and market share .